Understanding Interaction Search Behavior in Professional Social Networks - Harr, Rikard; Wiberg, Mikael; Whittaker, Steve (Human Technology, 2011)
We present an empirical study of social interaction in a professional social network. As the point of departure, we take previous research into distributed work and information foraging theory to explore interaction search behavior of individuals active in professional networks, examining how social factors govern their behavior. For this exploration, we focused on the process through which relevant collaborators are chosen to execute shared work tasks in the area of logistics, and identified six characteristics of the explored processes. We recognized the "survival of the social" as a cornerstone for efficient and long-term professional networks and outlined design implications arising from our findings. More specifically, we found that participants are oriented to solutions that involve active social agents and social relations, rather than optimizing based on task characteristics, efficiency, and cost. These behaviors motivate the need for the concept of social interaction foraging.